Naval modernisation in South-East Asia nature, causes and consequences - Till, Geoffrey; Chan, Jane (Cass series: naval policy and history, 2014)
This edited volume analyses the naval arms race in South-East Asia, and reviews the content, purposes and consequences of the naval policies and development of the main countries of the region.The rise of naval capability in the countries of the Asia-Pacific Region is increasingly recognised as a major indicator of the 'rise of Asia' and its increasing importance in the world's political, economic and strategic future. Most coverage focusses solely on the navies of the 'big four' - the US, China, India and Japan; however, the region's other navies, though much smaller, are significant too. Given the current focus on the South China Sea and the Obama administration's pivot to Asia, naval development in South-East Asia is of particular relevance